Traditional antidiabetic plants from Indonesia - Hartanti, Dwi; Budipramana, Krisyanti (Ethnobotany Research and Applications, 2020)
Background: Indonesia with its widely varied geographical features is rich with knowledge and practice in the utilization of plants for maintaining health and treating diseases, including for diabetes mellitus. This review summarizes the result of ethnopharmacological studies mentioning the application of plants to treat diabetes mellitus conducted in Indonesia. Methods: The online literature search using Google Scholar (https://scholar.google.com/) was carried out to collect data on the use of plants for traditional treatment of diabetes mellitus from ethnobotanical studies in Indonesia published in 2014-2018. Results: The traditional medicinal plants listed in this article are compiled from 67 studies conducted in 18 provinces and 37 defined ethnicities. There are 132 species of antidiabetic plants from 53 families reported. The most popular plants with multiple uses in different places include Orthosiphon aristatus (Blume) Miq., Persea americana Mill., and Syzygium polyanthum (Wight) Walp. Leaves, decoction, and oral were found to be the most frequently used plant parts, preparation method, and administration route of those antidiabetic plants, respectively. Conclusions: Indonesia has a large number of traditional antidiabetic plants that are potentially developed further into standardized herbal medicines to enable their uses in formal healthcare systems. Keywords: Ethnopharmacology, Indonesia, medicinal plants, antidiabetic activities, antidiabetic compounds.